The Treatment of Low Leg Nonischemic Ulcers With a Traditional Chinese-Pharmaceutical Medium: A Randomized Controlled Multicenter Clinical Study. (June 2019) - Zhang, Jun; Chen, Xu; Yu, Linxiang; Xue, Jingxian; Zhu, Zhiyuan; Wang, Cong; Tang, Tian; Feng, Zeyu; Yao, Chang
The aim of this study was to observe the curative effect and mechanism of Shengji Yuhong ointment in the healing of chronic ulcer of lower limbs. 400 patients were equally divided into treatment group and control group. The treatment group was covered with a piece of Shengji Yuhong ointment gauze, while the control group was covered with a piece of Vaseline gauze. Both groups changed dressings every other day for 4 weeks. On the 3rd, 7th, 14th, 21st, and 28th days of treatment, the reduction rate of wound area and the growth of wound granulation were observed and the levels of hydroxyproline and hemoglobin in wound granulation tissue were measured. The total effective rate was 99.00% in the treatment group and 71.00% in the control group. The treatment group was significantly better than the control group ( P < .01). The ulcer area reduction rate of the treatment group was significantly higher than that of the control group ( P < .01). The scores of ulcer depth, granulation color, and coverage area on the 7th, 14th, 21st, and 28th days after treatment in the treatment group were significantly lower than those before treatment ( P < .05). After treatment, the levels of hydroxyproline and hemoglobin in granulation tissue of wounds in both groups were significantly higher than those before treatment ( P < .01), and the levels in the treatment group were significantly higher than those in the control group ( P < .01). Shengji Yuhong ointment can improve the healing rate of chronic ulcer of lower limbs.